Amyloid‐beta is a cytokine. (1st February 2022) - Weaver, Donald F; Meek, Autumn
Abstract: Background: A molecular level conceptualization of the pathogenesis of Alzheimer's disease (AD) remains elusive. There are many different mechanistic proposals including proteopathy, tauopathy, immunopathy, gliopathy, mitochondriopathy, synapopathy. The two leading contenders are the amyloid protein misfolding hypothesis (proteopathy), and the innate immunotoxicity hypothesis (immunopathy). However, arising from multiple much‐publicized failures of amyloid‐targeting therapies, some researchers have declared "the amyloid hypothesis is dead", proclaiming the need to focus exclusively on other avenues such as immunopathy. But this need not be an "either‐or" situation; indeed, if β‐amyloid (Aβ) is regarded as simply an early responder cytokine, then proteopathic considerations become encompassed within an overarching hybrid proteopathic‐immunopathic mechanism, embracing the comprehensive role of innate immunity in the etiopathogenesis of AD. Method: Molecular modelling simulations have been done to explore Aβ at the molecular level. First, detailed simulations were performed demonstrating that Aβ binds to and penetrates model membranes analogous to an antimicrobial peptide (AMP); second additional in silico simulations demonstrated that Aβ is structurally and functionally similar to chemokines, and like chemokines has a BBXB (B is any basic amino acid) motif that enables it to bind to glycosaminoglycans. Result: Aβ is a molecular constituent of the innate immune system. Aβ is an antimicrobial peptide functioning not only as a killer peptide, but also a modulatory immunopeptide. Aβ satisfies the definition of a cytokine and exhibits interdependency with other cytokines characterized by pleotropism, redundancy and synergism. Aβ also satisfies the functional definition of a chemokine, but not the strict structural definition; Aβ exists within the AMP‐chemokine spectrum also exhibiting oligomerization and binding to GAGs via its HHQK(BBXB) motif. Conclusion: Within the context of AD disease pathogenesis, Aβ may be regarded as an early responder cytokine. This simplifies the complex collaborative connections between Aβ and the established anti/pro‐inflammatory cytokines of innate immunity, and enables incorporation of amyloid misfolding into the evolving immunopathic disease mechanism hypotheses of AD.